Intensitas Serangan Penyakit Penting pada Beberapa Galur Jagung Manis (Zea mays Var. saccharata Sturt) MS-UNSIKA Generasi M8 - Sulastri, Sindy; Surjana, Tatang; Syafi'i, Muhammad (UNIVERSITAS LABUHANBATU, 2024)
Sweet corn is a holticultural that has an important role as a national food source. Corn serves as an alternative food after rice that is commonly consumed by people in Indonesia. One of the causes of decreased sweet corn productivity is attack on corn plant disease. Some important disease that attack sweet corn is leaf blight and leaf rust. Use a genetically mutated varieties resistant to these diseases is one of solution to increase sweet corn production caused by disease attack. This study aims to obtain the lowest intensity of important disease and the best production result in the MS-UNSIKA generation M8 sweet corn. The research was conducted in one of the lands of Kalihurip Village, Cikampek sub District, Karawang District, from February 2024 to Mei 2024. The research method used was an experimental method, using a Single Factor Randomized Block Design (RAK) consisting of 6 MS-UNSIKA M8 sweet corn lines and 4 comparison varieties which were repeated 3 times in plots measuring 2 m x 2 m.. The results of the study showed significantly different effects of leaf blight attacks at 42 and 49 HST, and leaf rust disease at 56 and 63 HST. The Maestro and Bonanza varieties are the varieties that have the lowest attacks of leaf blight and rust with an average attack intensity of21.40% and 11.08% respectively. The results of this research also show that there is no correlation between leaf blight attacks on the production of sweet corn lines (Zea mays Var. saccharata Sturt). Keywords: sweet corn, leaf blight, leaf rust, important diseease